Road Damage Analysis Using the AHP (Analytical Hierarchy Process) Method as the Basis for Road Handling Programs on Provincial Roads in Pacitan Regency - Fuad Jauhar Zuhri; Andi Patriadi; Sajiyo Sajiyo (TRANSPUBLIKA INTERNATIONAL RESEARCH IN EXACT SCIENCES, 2025)
Land transportation infrastructure, such as roads and bridges, plays a crucial role as a link between regions that supports the economic, social, and cultural growth of a region. With limited budget in road management in Pacitan Regency, priority determination is needed to ensure that road management is carried out more efficiently and on target. This study aims to calculate the weight of the criteria using the Analytical Hierarchy Process (AHP) method based on expert opinions and to determine the priority order of road management in Pacitan Regency by utilizing the Provincial/Regency Road Management System (PKRMS) application, the AHP method, and a combination of the two methods. The method used in this study involves AHP with six criteria, namely road conditions, traffic volume, road connectivity, regional development, connecting economic and agricultural areas, and connecting public service facilities. This study focuses on five road sections in Pacitan Regency. The results of the study show that based on the AHP method, the road connectivity criterion gets the highest weight of (35%), followed by connecting public service facilities (22%), road conditions (14%), connecting economic and agricultural areas (13%), regional development (12%), and traffic volume (4%).